2023
DOI: 10.1021/acsami.3c00498
|View full text |Cite
|
Sign up to set email alerts
|

Ti–Si–Zr–Zn Nanometallic Glass Substrate with a Tunable Zinc Composition for Surface-Enhanced Raman Scattering of Cytochrome c

Abstract: As a remarkably powerful analytical technique, surface-enhanced Raman scattering (SERS) continues to find applications from molecular biology and chemistry to environmental and food sciences. In search of reliable and affordable SERS substrates, the development has moved from noble metals to other diverse types of structures, e.g., nano-engineered semiconductor materials, but the cost of the enhancement factors (EF) substantially decreasing. In this work, we employ biocompatible thin films of Ti–Si–Zr–Zn nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The conducted XRD analysis indicated that no sharp diffraction peaks corresponding to the crystalline phases were detected in the as-anodized ZACO (Figure b). The appearance of a visible broad hump in the XRD pattern of ZACO confirms the amorphous character, which has been proven to be positive for enhancing SERS signals . The EDS analysis of ZACO in Figure (c) confirmed the presence of Zr, Al, Co, and O elements, with the corresponding atomic percentages of 28, 7, 12, and 53%.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…The conducted XRD analysis indicated that no sharp diffraction peaks corresponding to the crystalline phases were detected in the as-anodized ZACO (Figure b). The appearance of a visible broad hump in the XRD pattern of ZACO confirms the amorphous character, which has been proven to be positive for enhancing SERS signals . The EDS analysis of ZACO in Figure (c) confirmed the presence of Zr, Al, Co, and O elements, with the corresponding atomic percentages of 28, 7, 12, and 53%.…”
Section: Resultsmentioning
confidence: 54%
“…Thus, in the water-rich Cyt c solution with a lower amount of P 6 M (0.005 g), the cations and anions are highly dissociated, and the dissociation extent is larger in comparison with that possessing a higher concentration of P 6 M (0.01 g). It should be noted that the concentration of the IL is lower in Cyt c –P 6 M (0.005)–ZACO than in Cyt c –P 6 M–ZACO (0.01 g IL), resulting in less free ions in the system with 0.005 g of P 6 M that contribute to ionic conductivity, not beneficial to the charge-transfer process, and thus the SERS performance . However, a further increase of P 6 M to 0.05 g led to an increased association of cation–anion pairs and thus less free ions contributing to ionic conductivity, ultimately resulting in weaker SERS signals of Cyt c .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the high expense associated with noble metals, researchers have explored alternative materials for constructing SERS substrates. Particularly, semiconductor materials have been demonstrated to have high stability, cost effectiveness, and enhanced biocompatibility . Nowadays, many kinds of semiconductor materials, such as graphene and its derivatives, transition metal oxides, and metal–organic composites, have been studied as material choices of SERS substrates and exhibited considerable SERS activity. However, achieving reproducible and repeatable SERS enhancement along with accurately interpreting SERS signals remain significant challenges due to variable particle size, morphology, random distribution, and uncontrollable nanoparticle aggregation .…”
Section: Introductionmentioning
confidence: 99%